ANALYSIS OF ACADEMIC PROCRASTINATION (AN OVERVIEW THROUGH SELF-REGULATION AND SELF-EFFICACY) IN ACCOUNTING STUDENTS AT VOCATIONAL HIGH SCHOOLS - Sukma, Novianny; Fauzi, Achmad; Mardi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The objective of this research is to investigate the effect of self-regulation on learning and self- efficacy partially or simultaneously on academic procrastination at State Vocational High Schools in East Jakarta. The method used in this research is a quantitative method. The population of this study was 179 students with 124 students who used as a research sample using the Proportionate Stratified technique Random Sampling. To obtain data the research used primary data in the form of a questionnaire / questionnaire. The research results show that self-regulation variables in learning have a significant negative effect on academic procrastination. The self-efficacy variable also has a negative and significant effect on academic procrastination. Simultaneously, the variables of self-regulation in learning and self-efficacy have an influence on academic procrastination in students of State Vocational Schools in East Jakarta. Test results from the coefficient of determination is 77.9%, while the rest is influenced by other factors outside the study. Hence, this study concluded that there is an influence between self-regulation in learning and self-efficacy on academic procrastination in XII grade of accounting students at State Vocational High Schools in East Jakarta.